2008
DOI: 10.1136/jech.2007.063016
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to depression during pregnancy: are there gender differences?

Abstract: Most predictor factors of depression during pregnancy are similar for both sexes but a gender-different impact of social support and partner depression on pregnancy depression was appreciated. Health professionals should be aware of potentially vulnerable groups for early diagnosis of pregnancy depression and to provide effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 43 publications
7
65
0
6
Order By: Relevance
“…This is one of the first studies to report the prevalence of antenatal depressive symptoms in a sample of Canadian men. Previous studies on paternal antenatal depression have reported prevalence rates ranging from 6.4% to 11.5% (Escribà-Agüir & Artazcoz, 2011; Escribè-Agüir, Gonzalez-Galarzo, Barona-Vilar, & Artazcoz, 2008;Figueiredo & Conde, 2011;Gawlik et al, 2014;Teixeira et al, 2009). Figueiredo and Conde (2011) using a cutoff score of ≥10 on the EDS reported a rate of 11.5% for expectant fathers in early pregnancy which increased in each trimester, particularly for first-time fathers, while Teixeira et al (2009) reported a rate of 6.4% in the third trimester which declined from 11.3% in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first studies to report the prevalence of antenatal depressive symptoms in a sample of Canadian men. Previous studies on paternal antenatal depression have reported prevalence rates ranging from 6.4% to 11.5% (Escribà-Agüir & Artazcoz, 2011; Escribè-Agüir, Gonzalez-Galarzo, Barona-Vilar, & Artazcoz, 2008;Figueiredo & Conde, 2011;Gawlik et al, 2014;Teixeira et al, 2009). Figueiredo and Conde (2011) using a cutoff score of ≥10 on the EDS reported a rate of 11.5% for expectant fathers in early pregnancy which increased in each trimester, particularly for first-time fathers, while Teixeira et al (2009) reported a rate of 6.4% in the third trimester which declined from 11.3% in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition to the impacts on mother and child, findings have shown that there are links between women's depression and their partner's mental health. 29,30 In men, partner depression has been found to be associated with a higher probability of reporting depression, 29 and PND in men has been reported as associated with depression in their partners during pregnancy and after delivery. 30 …”
Section: Significance For Patients In Terms Of Illhealth (Burden Of Dmentioning
confidence: 99%
“…Sessions including partners were rated as important, and as previous research has shown that there is a detrimental impact on the partners of women with PND 29,30 this may be a particularly important area for future research. A related concern is the impact of PND on other family members including the infant and siblings.…”
Section: Suggested Research Prioritiesmentioning
confidence: 99%
“…The prevalence of antenatal depression ranges between 10% and 20%, depending on the population studied and the stage in pregnancy [1,2]. Anxiety during pregnancy is also common, and is experienced by 12% to 60% of women [3,4].…”
Section: Introductionmentioning
confidence: 99%